A Heuristic Approach for Two-Dimensional Rectangular Cutting Stock Problem considering Balance for Material Utilization and Cutting Complexity - Dianjian Wu; Guangyou Yang (Advances in Materials Science and Engineering)
The common staged patterns are always required during the cutting process for separating a set of rectangular items from rectangular plates in manufacturing industries. Two-staged patterns can reduce cutting complexity at the expense of material utilization; three-staged patterns do the opposite. Combining these two types of staged patterns may be a good balance for two contradictory objectives of material utilization and cutting complexity. A heuristic approach is proposed to solve the two-dimensional rectangular cutting stock problem with a combination of two-staged general patterns (2SGP) and three-staged homogenous patterns (3SHP). Firstly, the 2SGP and 3SHP are constructed by using recursive techniques. The pattern with the larger value is selected as the candidate pattern. Then, the value of each item is corrected according to the current candidate pattern. A cutting plan accurately satisfying all items demand is obtained by using the sequential heuristic algorithm. Finally, the cutting plan with a minimum number of used plates is achieved by applying the iterative algorithm. The computational results indicate that the proposed heuristic approach is more effective in material utilization and cutting complexity than the two published algorithms with staged patterns.